Challenges of a community based pragmatic, randomised controlled trial of weight loss maintenance. (December 2015) - Randell, Elizabeth; McNamara, Rachel; Shaw, Christine; Espinasse, Aude; Simpson, Sharon
Abstract Background Randomised controlled trials (RCTs) have a reputation for being inherently difficult to deliver as planned and often face unforeseen challenges and delays, particularly in relation to organisational and governance difficulties, participant interest, constraints due to allocation of costs, local investigator interest and lengthy bureaucracy. Recruitment is often difficult and the challenges faced often impact on the cost and delivery of a successful trial within the funded period. This paper reflects upon the challenges faced in delivering a pragmatic RCT of weight loss maintenance in a community setting and suggests some potential solutions. Methods The weight loss maintenance in adults trial aimed to evaluate the impact of a 12 month, individually tailored weight maintenance intervention on BMI 3 years from randomisation. Participants were recruited primarily from participant identification centres (PICs)—GP surgeries, exercise on referral schemes and slimming world. The intervention was delivered in community settings. A recruitment strategy implementation plan was drafted to address and monitor poor recruitment. Results Delays in opening and recruitment were experienced early on. Some were beyond the control of the study team such as; disagreement over allocation of national health service costs and PIC classification as well as difficulties in securing support from research networks. That the intervention was delivered in community settings was often at the root of these issues. Key items to address at the design stage of future trials include feasibility of eligibility criteria. The most effective element of the recruitment implementation plan was to refocus sources of recruitment and target only those who could fulfil the eligibility criteria immediately. Conclusions Learnings from this trial should be kept in mind by those designing similar studies in the future. Considering potential governance, cost and research network support implications at the design stage of pragmatic trials of any community-based complex intervention is paramount. The appropriateness and viability of inclusion criteria also require careful consideration as does use of a targeted advertising strategy. Trial registration : ISRCTN35774128, 12/01/2010